Surgery for massive paediatric head and neck Neurofibroma: two case reports - Asha'ari, Zamzil Amin; Abdullah, Kahairi; Shahid, Hassan (Faculty of Medicine, International Islamic University Malaysia, 2012)
We report two paediatric patients with massive head and neck plexiform neurofibromas who underwent surgical excision. We wish to highlight issues and implications pertaining to the surgery, in particular, the management of intraoperative bleeding often encountered in these cases.